The relevance of Bernard Lonergan's notion of self-appropriation to a mystical-political theology - Bell, Ian B. (American university studies / 7, 2008)
Mystical-political theology -- Mysticism -- Evelyn Underhill -- William Johnston -- Political theology -- Gustavo Gutierrez -- Dorothee Sille -- Self-appropriation I : patterns of experience -- Biological pattern of experience -- Aesthetic pattern of experience -- Intellectual pattern of experience -- Dramatic pattern of experience -- Practical pattern of experience -- Worshipful pattern of experience -- Mystical pattern of experience -- Self-appropriation II : operations of the human subject -- Operations of the human subject -- Experiencing -- Understanding -- Judging -- Objectivity of knowing -- The role of definitions in judging -- The role of probability in judging -- Self-correcting nature of human knowing -- Common sense -- The relationship between common sense and theory -- Decision -- Freedom in deciding -- Kataphatic mysticism and the operations of the human subject -- Unity in differentiation: the spiritually integrated subject -- Self-appropriation III : conversion and the dialectic of the subject -- Conversion -- Intellectual conversion -- Religious conversion -- Moral conversion -- Feelings -- Implications of moral conversion -- The relationship between the conversions -- Dialectic of the subject -- Mysticism and the healing vector -- A clarification by contrast -- Self-appropriation and the theologian -- Self-appropriation and the mystical theologian -- Mystical theology as reflection upon personal mystical experience -- Mystical theology as the study of mystical texts -- Mystical theology as reflection on personal experience and tradition -- Self-appropriation and political theology -- Structure of the human good -- The early period -- The later period -- Self-appropriation and the human good